Mafhum Yûsuf Al-Qardhâwî ‘An At-Tafsîr Al-‘Ilmî (Dirâsah fî Al-Jânib Al-Unthûlûjî) - Ahmad Fadly Rahman Akbar; Abdul Ramli Hasan (Studia Quranika, 2020)
“Tafsir Ilmi” is a new characteristic of “tafsir” which was famous in this era. There are many contemporary problems of “tafsir ilmi”. It is required a thought of contemporary scholar whose able to solve it. He is Yûsuf Al-Qardhâwî who has devoted his thought to solve it. He is specialist in jurisprudence but it was not in authority of Al-Qur’an and tafsir. Eventhough, he has researched in tafsir ilmi and owned several works in Al-Qur’an and tafsir. This research shows that Yûsuf Al-Qardhâwî’s thought in tafsir ilmi (especially ontological aspect) comprehends: First, existence of “tafsir ilmi” and “i’jaz ilmi”; Second, the reality of “tafsir ilmi” and “i’jaz ilmi”; Third, the connection between “tafsir ilmi” and “i’jaz ilmi”; Fourth, Yûsuf Al-Qardhâwî’s position in dialectics of tafsir ilmi.